Exploratory Study on Trauma Scoring Systems for SAVE Triage - Uhm, Tai-Hwan; Kim, Jee Hee; Park, Sang-Kyu; Kwag, Eun-Jwoo; Kim, Mi-Sook; Shin, So-Yeon (Fire Science and Engineering, 2020)
This study examined several trauma scoring systems that serve as the basis for applying the Secondary Assessment of Victim Endpoint (SAVE) severity classification to propose a method that can be applied during triage. By using an exploratory method, data collected from different trauma scoring systems was qualitatively evaluated. First, it was confirmed that the survival risk ratio (SRR) of the International Classification of Disease-based Injury Severity Score (ICISS) can be used for SAVE severity classification. Second, the Korean Trauma Data Bank (KTDB) of the Central Emergency Medical Center does not indicate the SRR of each injury according to the Korean standard classification of disease and cause of death (KCD). Third, the SRR of injuries, from data acquired from the United States can be used for classification of SAVE severity classification. Fourth, the addition of SRR from the KCD to the KTDB can be used for SAVE severity classification.